Cytokinin Oxygenase/Dehydrogenase Inhibitors: An Emerging Tool in Stress Biotechnology Employed for Crop Improvement - Arora, Kavita; Sen, Sangeeta (Frontiers in Genetics, 2022)
To meet the global challenges of food security, one of the foremost solutions lies in enhancing the crop productivity. This can be attained by considering key plant hormones such as cytokinins as agrochemicals as cytokinins control the essential processes of the plants. Since 1980s, it has already been established that the enzyme, cytokinin oxidase/dehydrogenase (CKO/CKX) deactivates cytokinins; however, the potential application of manipulating these enzymes have mostly been speculated to have a high potential in the biotechnology industry. This enzyme is critical in maintaining a balanced level of cytokinins in plants. However, it is yet to be fully established that inhibiting this enzyme can be the constant source of improvement in the productivity of plants, even though success has been obtained in some economically important plant species. Furthermore, the effectivity of the impact of this enzyme may vary from plant to plant, which needs to be evaluated employing tissue culture and other extrinsic applications. This review intends to cover the relevant studies addressing any biological activity of this enzyme in the current context and any associated biotechnological applications specific to enhanced grain yield, abiotic stress tolerance, delayed senescence and in vitro organogenesis among various plants and not only cereals. Moreover, our study will identify the present gaps in research with respect to many important food crops, which will be useful for researchers who are actively involved in providing a foundation for a variety of genetically improved plants achieved through this manner.